Silicon-carbon composite material as well as preparation method and application thereof

By achieving gradient distribution of silicon particles in porous carbon materials, and combining silicon dioxide layer and carbon cladding layer, the problems of existing silicon-carbon composite materials in volume expansion stress buffer, silicon particle utilization and conductivity are solved, and the cycle life and rate performance of lithium-ion batteries are significantly improved.

CN119542394APending Publication Date: 2025-02-28SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411719967.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

There are many problems in existing silicon-carbon composite materials in terms of structure and performance, including difficulty in forming an effective volume expansion stress buffering mechanism, low utilization of silicon particles, poor material circulation stability, low rate performance and fast capacity attenuation.

Method used

Porous carbon materials are used as the matrix, and the silicon particles are distributed gradiently in the surface layer and internal pores of the porous carbon materials. The distribution concentration and particle size of the surface silicon particles are smaller than that of the inside, forming a silicon dioxide layer and a carbon cladding layer to alleviate the problem of volume expansion and improve the conductivity.

Benefits of technology

Through the combination of gradient-distributed silicon particles and porous carbon materials, the cycle life, rate performance and capacity retention of the battery are significantly improved, and the stability and conductivity of the electrode structure are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542394A_ABST
    Figure CN119542394A_ABST
Patent Text Reader

Abstract

The invention provides a silicon-carbon composite material as well as a preparation method and application thereof. The silicon-carbon composite material comprises a porous carbon material; the silicon particles are distributed on the surface layer of the porous carbon material and in pore channels in the porous carbon material, the distribution concentration of the silicon particles in the surface layer of the porous carbon material is smaller than that of the silicon particles in the porous carbon material, and the particle size of the silicon particles in the surface layer of the porous carbon material is smaller than that of the silicon particles in the porous carbon material; the silicon dioxide layer is formed on the surface of the silicon particles; and the carbon coating layer is formed on the surface of the silicon dioxide layer. The lithium ion battery prepared by taking the silicon-carbon composite material as a positive electrode active material shows good electrochemical performance, and has relatively high specific capacity, good cycling stability and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new energy technology, and specifically relates to a silicon-carbon composite material and a preparation method and application thereof. Background Art

[0002] As one of the most important rechargeable batteries, lithium-ion batteries are widely used in portable electronic devices, electric vehicles, and renewable energy storage. With the increasing market demand for high-energy density batteries, the theoretical capacity limit of traditional graphite anode materials (372mAh / g) can no longer meet the requirements. Silicon, as a potential high-capacity anode material (theoretical capacity up to 4200mAh / g), has attracted widespread attention from researchers. However, silicon-based anode materials face serious volume expansion problems in practical applications. During the charge and discharge process, the volume of silicon can expand by up to 300%, which can easily lead to electrode structure destruction, active material shedding, and electrolyte decomposition, resulting in rapid battery capacity decay and short cycle life. To solve these problems, researchers have proposed a variety of strategies, among which silicon / carbon composites are favored due to their good structural stability and conductivity.

[0003] However, the silicon-carbon composite materials in the prior art still have many problems in terms of structure and performance. For example, the current common structural design of silicon-carbon negative electrode materials is to make silicon particles evenly distributed in the carbon material. This structure is difficult to form an effective volume expansion stress buffer mechanism, which is easy to cause structural damage to the material, and the utilization rate of silicon particles inside the carbon material is low, and the high specific capacity advantage of silicon cannot be fully utilized. In addition, there are some silicon-carbon negative electrode materials prepared by the prior art, in which the silicon particles are mainly concentrated on the surface of the carbon material. The defect of this structure is that the surface silicon particles are prone to volume expansion and shedding during the cycle, and the structural stability is poor, resulting in rapid attenuation of the material capacity. In addition, the silicon particles on the surface of the silicon-carbon composite materials prepared by traditional preparation methods such as mechanical ball milling and gas phase method are prone to aggregation and growth to form large-sized particles. These large particles are prone to volume expansion and shedding during the charge and discharge process, reducing the cycle stability of the material. Summary of the invention

[0004] In order to solve all or part of the above technical problems, the present invention provides the following technical solutions:

[0005] One of the purposes of the present invention is to provide a silicon-carbon composite material, comprising:

[0006] Porous carbon materials;

[0007] Silicon particles, wherein the silicon particles are distributed in the surface layer and the pores inside the porous carbon material, and the distribution concentration of the silicon particles in the surface layer of the porous carbon material is less than the distribution concentration of the silicon particles inside the porous carbon material, and the particle size of the silicon particles in the surface layer of the porous carbon material is less than the particle size of the silicon particles inside the porous carbon material;

[0008] A silicon dioxide layer formed on the surface of the silicon particles;

[0009] A carbon coating layer is formed at least on the surface of the silicon dioxide layer.

[0010] The present invention provides a silicon-carbon composite material having a gradient distribution characteristic of silicon particles, wherein the silicon particles distributed on the surface of the porous carbon material are relatively small and have a relatively small particle size, and the silicon particles distributed inside the porous carbon material are relatively large and have a relatively large particle size, and such a structure is conducive to the silicon-carbon composite material to relieve surface stress and form a stress gradient; and it can also improve the utilization rate of internal silicon particles, optimize ion transmission and improve electronic conduction. In addition, the silicon dioxide layer and the carbon coating layer in the silicon-carbon composite material provided by the present invention can further alleviate the volume expansion problem of the battery during the charging and discharging process, and improve the stability of the electrode structure; the conductive network jointly constructed by the porous carbon material and the carbon coating layer can enhance the conductive performance of the electrode; the silicon-carbon composite material is used to prepare the negative electrode of a lithium-ion battery to improve the cycle life, rate performance and capacity retention rate of the battery.

[0011] In some embodiments, the thickness of the surface layer of the porous carbon material is 1-10% of the diameter of the porous carbon material, and the interior of the porous carbon material is the area of ​​the porous carbon material excluding the surface layer.

[0012] In some embodiments, the diameter of the porous carbon material is 1 to 10 um, the region of the porous carbon material that is 0 to 100 nm away from the surface is the surface layer of the porous carbon material, and the region that is more than 100 nm away from the surface of the porous carbon material is the interior of the porous carbon material. The silicon particle distribution concentration of the surface layer of the porous carbon material of the present invention refers to the ratio of the mass of silicon particles in the surface layer to the mass of the porous carbon material in the surface layer region, and the silicon particle distribution concentration inside the porous carbon material of the present invention refers to the ratio of the mass of silicon particles inside to the mass of the porous carbon material in the internal region.

[0013] In some embodiments, the distribution concentration ratio of the silicon particles on the surface of the porous carbon material to the silicon particles inside the porous carbon material is 1:2 to 1:5.

[0014] In some embodiments, the ratio of the total mass of silicon particles contained in the silicon-carbon composite material to the mass of the porous carbon material is 0.5:1 to 2:1.

[0015] In some embodiments, the particle size of the silicon particles on the surface of the porous carbon material is 1 to 5.8 nm, preferably 2.3 to 5.8 nm, and the particle size of the silicon particles inside the porous carbon material is 1 to 11.2 nm, preferably 6.3 to 11.2 nm.

[0016] In some embodiments, the specific surface area of ​​the porous carbon material is 500 to 3000 m 2 / g.

[0017] In some embodiments, the total pore volume of the porous carbon material is 0.6 to 1.2 cm 3 / g, the proportion of micropores with a pore size of less than 2nm in the porous carbon material is 40-60% of the total pore volume of the porous carbon material, the proportion of mesopores with a pore size of 2-50nm is 30-50% of the total pore volume of the porous carbon material, and the proportion of macropores with a pore size greater than 50nm is 5-15% of the total pore volume of the porous carbon material. The larger specific surface area of ​​the porous carbon material is conducive to increasing the loading amount and dispersion of silicon, and the higher porosity is conducive to the highly dispersed deposition of silicon and the penetration of the electrolyte.

[0018] In some embodiments, the thickness of the silicon dioxide layer is 1 to 2 nm. If the thickness of the silicon dioxide layer is too small, it will lead to insufficient protection of the silicon particles, and it will not be able to effectively alleviate the volume expansion of the silicon particles during the charge and discharge process, which is easy to cause structural damage and performance degradation; if the thickness of the silicon dioxide layer is too large, it will lead to a decrease in the specific capacity of the silicon particles, and increase the lithium ion transmission resistance, affecting the rate performance of the material.

[0019] In some embodiments, the thickness of the carbon coating layer is 2 to 30 nm. If the thickness of the carbon coating layer is too small, the protection of the silicon particles will be insufficient, and the direct contact with the electrolyte cannot be effectively prevented, which may cause side reactions and capacity decay; if the thickness of the carbon coating layer is too large, the lithium ion transmission path will be extended, affecting the charge and discharge rate, and also reducing the specific capacity of the overall material.

[0020] A second object of the present invention is to provide a method for preparing a silicon-carbon composite material, comprising:

[0021] Loading a catalyst on the surface and inside of the porous carbon material, wherein the concentration of the catalyst in the surface of the porous carbon material is lower than the concentration of the catalyst inside the porous carbon material, to obtain a porous carbon material containing a gradient concentration of catalyst;

[0022] Silicon particles are deposited on the porous carbon material containing the gradient concentration catalyst by a vapor deposition method, thereby obtaining a first intermediate material; the silicon particles in the first intermediate material are distributed in the surface layer and the pores inside the porous carbon material, and under the action of the gradient concentration catalyst, the distribution concentration of the silicon particles in the surface layer of the porous carbon material is less than the distribution concentration of the silicon particles inside the porous carbon material, and the particle size of the silicon particles in the surface layer of the porous carbon material is less than the particle size of the silicon particles inside the porous carbon material;

[0023] Performing a pre-oxidation treatment on the first intermediate material so that the silicon on the surface of the silicon particles is oxidized to form a silicon dioxide layer, thereby obtaining a second intermediate material;

[0024] The second intermediate material is carbon-coated to form a carbon coating layer on the silicon dioxide layer to obtain a silicon-carbon composite material.

[0025] The present invention finds that silicon particles formed by traditional chemical vapor deposition methods or physical vapor deposition methods tend to aggregate and grow on the surface of carbon materials, forming large-sized silicon particles on the surface. These large-sized silicon particles expand dramatically in volume during the charge and discharge process, causing material structure destruction and active material shedding, and also blocking the pore structure of the carbon material, affecting the penetration of the electrolyte and ion transport. The preparation method provided by the present invention first forms a catalyst with a gradient concentration in the carbon material in a targeted manner, so that the formed silicon particles not only have the characteristics of a gradient concentration distribution, but also can avoid the formation of large-particle silicon on the surface of porous carbon materials, solve the problems of poor cycle stability, low rate performance and fast capacity decay due to the aggregation of large-sized silicon particles in the prior art, and improve the cycle life, rate performance and capacity retention rate of the battery.

[0026] In some embodiments, the step of loading the catalyst on the surface and interior of the porous carbon material specifically includes: first immersing the porous carbon material in a solution containing 0.01-0.1 mol / L of a catalyst precursor for 2-6 hours, and then immersing the porous carbon material in a solution containing 0.5-1 mol / L of a catalyst precursor for 0.5-2 hours; and controlling the temperature of the solution to 20-80°C during the immersion process to obtain a porous carbon material containing a catalyst precursor; and pyrolyzing the porous carbon material containing the catalyst precursor to convert the catalyst precursor therein into a catalyst to obtain a porous carbon material containing a gradient concentration of catalyst.

[0027] The porous carbon material is impregnated with low-concentration and high-concentration catalyst precursor solutions in steps to form a concentration gradient of the catalyst precursor in the porous carbon material, and the catalyst precursor is converted into a catalyst in situ in combination with pyrolysis treatment. The formation of a catalyst concentration gradient by step-by-step impregnation in different areas of the porous carbon material is due to the fact that surface tension and adsorption promote the migration and accumulation of the catalyst into the interior of the carbon material, and the cumulative effect of multiple impregnations gradually strengthens the catalyst concentration inside the carbon material.

[0028] In some embodiments, the step of loading the catalyst on the surface and interior of the porous carbon material specifically includes: first immersing the porous carbon material in a solution containing 0.01-0.1 mol / L of a catalyst precursor, and then adding the catalyst precursor to the solution at intervals of 15-30 min until the concentration of the catalyst precursor in the solution reaches 0.2-1 mol / L, and maintaining the immersion at the final concentration for 2-6 h; during the immersion process, raising the temperature of the solution from room temperature to 60-80°C at a heating rate of 2-5°C / min; and pyrolyzing the porous carbon material containing the catalyst precursor to convert the catalyst precursor therein into a catalyst, thereby obtaining a porous carbon material containing a gradient concentration catalyst.

[0029] In some embodiments, the pyrolysis treatment is carried out under inert atmosphere conditions, the temperature of the pyrolysis treatment is 400-900° C., and the time is 1-5 hours.

[0030] In some preferred embodiments, the pyrolysis treatment specifically includes: first treating at a temperature of 400-600°C for 1-2 hours, and then heating to 700-900°C for 1-3 hours. The pyrolysis treatment using the temperature gradient can first remove the functional groups on the surface of the porous carbon material, and then promote the reduction and dispersion of the catalyst, while maintaining the pore structure of the carbon material.

[0031] In some preferred embodiments, the preparation method further comprises: before immersing the porous carbon material in a solution containing a catalyst precursor, it also comprises modifying oxygen-containing functional groups and / or nitrogen-containing functional groups on the porous carbon material. Oxygen-containing functional groups (such as carboxyl groups, hydroxyl groups, etc.) and nitrogen-containing functional groups (such as amino groups) can form coordination effects with the catalyst precursor, thereby regulating the adsorption of the porous carbon material to the catalyst.

[0032] In some embodiments, the method for modifying oxygen-containing functional groups on the porous carbon material comprises: mixing the porous carbon material with an oxidant, stirring and reacting at 60 to 80° C. for 6 to 24 hours, and then washing and drying the oxidized porous carbon material. The oxidant comprises concentrated nitric acid or a mixed acid of nitric acid and sulfuric acid.

[0033] In some embodiments, the method for modifying nitrogen-containing functional groups on the porous carbon material comprises: mixing the porous carbon material with ammonia water, reacting at 150° C. for 4 to 8 hours, and then cooling, filtering, washing, and drying in sequence. The ammonia water concentration is, for example, 25 wt %.

[0034] In some embodiments, before the porous carbon material is impregnated in a solution containing a catalyst precursor, a porous polymer film with a pore size of 3 to 20 nm is used to wrap the porous carbon material to form an inclusion, and then the inclusion is impregnated in a solution containing a catalyst precursor. Wrapping the carbon material with a porous polymer film and then impregnating it can control the penetration rate of the catalyst precursor solution and avoid the rapid penetration of the precursor solution in the carbon material without forming a gradient concentration. The porous polymer film is preferably a degradable material, such as a polylactic acid porous polymer film or a polyhydroxybutyric acid porous film, which degrades during the subsequent pyrolysis process, thereby introducing impurities into the product without affecting the performance of the silicon-carbon negative electrode material.

[0035] In some preferred embodiments, the preparation method further comprises: performing ultrasonic treatment during the impregnation process, wherein the frequency of the ultrasound is 20 to 60 kHz and the ultrasound time is 5 to 30 minutes, so as to enable the catalyst precursor to penetrate into the porous carbon material more effectively.

[0036] In some embodiments, the catalyst includes copper and / or nickel. The catalyst precursor includes a soluble copper salt and / or a soluble nickel salt, such as copper nitrate, and a soluble nickel salt such as nickel nitrate, but not limited thereto.

[0037] In some embodiments, the mass concentration ratio of the catalyst in the surface layer of the porous carbon material to the catalyst in the interior thereof is 1:2 to 1:10.

[0038] In some embodiments, the vapor deposition method includes a plasma enhanced chemical vapor deposition method, and the process conditions of the plasma enhanced chemical vapor deposition include: using a pulsed gas intake method, alternately introducing a reaction gas containing a gaseous silicon source and an inert gas, and the gas flow ratio of the reaction gas to the inert gas is 1:5 to 1:20; the radio frequency power used is 50 to 500W, the pulse time is 1 to 60 seconds, the deposition temperature is 300 to 600°C, and the deposition time is 30min to 5h. Among them, the gas flow ratio of the reaction gas to the inert gas and the deposition time have an effect on the deposition depth of silicon particles in the pores of the porous carbon material. Within the range of 20 to 40% silane gas flow ratio and 2 to 5h deposition time, silane can be promoted to diffuse deeper into the pore structure of the carbon material.

[0039] The gaseous silicon source used in the plasma enhanced chemical vapor deposition method can be any silicon source in the prior art, such as silane, etc., and the present invention does not impose any particular limitation on this.

[0040] In some embodiments, the pre-oxidation treatment includes: placing the first intermediate material in an atmosphere with an oxygen content of 0.1 to 5 wt %, and pre-oxidizing at a temperature of 200 to 400° C. for 0.5 to 4 hours.

[0041] In some embodiments, the carbon coating method includes chemical vapor deposition, and the process conditions of the chemical vapor deposition method include: a flow rate of a gaseous carbon source of 50 to 250 sccm, a temperature of 700 to 950° C., and a time of 10 to 90 min. The gaseous carbon source used can be any carbon source in the prior art, such as acetylene, etc., and the present invention does not impose any particular limitation on this.

[0042] In some embodiments, the preparation method further includes post-treatment, which includes: heat treating the obtained silicon-carbon composite material under inert atmosphere conditions, the heat treatment temperature is 800-1100°C, and the time is 1-5 hours. The heat treatment can remove the unstable components or impurities remaining in the material, promote the rearrangement and optimization of the internal structure of the silicon-carbon composite material, and is conducive to forming a more uniform and dense microstructure; promote the bonding of the interface between the silicon and carbon components, and improve the overall performance of the composite material. Appropriate heat treatment can also relieve stress and improve conductivity.

[0043] In some embodiments, the post-treatment further comprises pickling the prepared silicon-carbon composite material with an acid solution to remove metal impurities therein. The pickling specifically comprises: pickling with 0.1-2 mol / L hydrochloric acid and / or nitric acid solution for 0.5-4 hours.

[0044] The third object of the present invention is to provide a silicon-carbon composite material, which is prepared by the method described in any one of the technical solutions.

[0045] A fourth object of the present invention is to provide an application of the silicon-carbon composite material in the preparation of a secondary battery negative electrode or a secondary battery.

[0046] A fifth object of the present invention is to provide a negative electrode for a lithium-ion battery, wherein the negative electrode for the lithium-ion battery comprises a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector, wherein the negative electrode active material layer comprises the silicon-carbon composite material.

[0047] The sixth object of the present invention is to provide a lithium ion battery, comprising a positive electrode, a negative electrode, an electrolyte and a separator, wherein the negative electrode is the negative electrode of the lithium ion battery.

[0048] Compared with the prior art, the present invention has at least the following beneficial effects:

[0049] (1) The distribution of silicon particles on the porous carbon material in the silicon-carbon composite material provided by the present invention has a gradient distribution characteristic, that is, the distribution concentration and particle size of silicon particles in the surface layer of the porous carbon material are smaller than the distribution concentration and particle size of silicon particles inside the porous carbon material. This structure is beneficial for the silicon-carbon composite material to relieve surface stress and form a stress gradient; improve the utilization rate of internal silicon particles, optimize ion transport and improve electron conduction, thereby improving the cycle life, rate performance and capacity retention rate of the battery.

[0050] (2) The silicon dioxide layer and the carbon coating layer in the silicon-carbon composite material can synergistically alleviate the volume expansion problem of silicon during the charging and discharging process, improve the stability of the electrode structure, and the conductive network jointly constructed by the porous carbon material and the carbon coating layer can significantly enhance the conductive performance of the electrode;

[0051] (3) The preparation method provided by the present invention can form a gradient concentration of the catalyst on the surface and inside of the porous carbon material, and combined with the vapor phase silicon deposition, it can promote the silicon particles in the porous carbon material to have the above-mentioned gradient distribution characteristics; and the preparation method can avoid the formation of large-sized silicon particles on the surface of the porous carbon material, solving the problem of easy aggregation of silicon particles on the surface of the carbon material in the prior art;

[0052] (4) The lithium-ion battery provided by the present invention exhibits excellent electrochemical properties, with high specific capacity, good cycle stability and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0054] Figure 1 is a cross-sectional view of a silicon-carbon composite material prepared in one embodiment of the present invention;

[0055] Figure 2 is an electron microscope image of a porous carbon material used in one embodiment of the present invention. DETAILED DESCRIPTION

[0056] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention. The specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.

[0057] Unless otherwise specified, the raw materials and reagents used in the specific embodiments of the present invention are all commercially available.

[0058] The surface layer of the porous carbon material described in the following embodiments and comparative examples refers to a region 0 to 100 nm away from the surface of the porous carbon material; the interior of the porous carbon material refers to a region greater than 100 nm away from the surface of the porous carbon material.

[0059] Example 1

[0060] Embodiment 1 provides a silicon-carbon composite material and a preparation method thereof, which specifically comprises the following steps:

[0061] (1) Take the specific surface area as 1500m 2 / g of activated carbon, immersed in a 0.1mol / L copper nitrate solution for 6h, and then transferred to a 1mol / L copper nitrate solution for immersion for 2h, maintaining the temperature of the copper nitrate solution at 50°C during the entire immersion process, to obtain an activated carbon material containing copper nitrate; in a nitrogen atmosphere, pyrolyzing the activated carbon material containing copper nitrate at 600°C for 1h to convert the copper nitrate therein into a copper catalyst, to obtain an activated carbon containing a copper catalyst;

[0062] The cross-sectional SEM-EDS analysis of the activated carbon material containing the copper catalyst prepared above showed that the copper therein had a gradient concentration characteristic, the copper concentration on the surface of the activated carbon was 1wt%, and the copper concentration inside the activated carbon was 3wt%;

[0063] (2) placing the activated carbon material containing the copper catalyst prepared above in a PECVD reaction chamber, and alternately introducing silane and argon by pulsed gas inlet, with a gas flow ratio of silane to argon of 1:10; setting the RF power to 200 W, the deposition temperature to 450 ° C, and the total deposition time to 2 hours; the pulse time is 10 seconds for silane and 30 seconds for argon, and the reaction obtains activated carbon deposited with silicon particles, which is recorded as the first intermediate material;

[0064] EDS line scan characterization analysis of the activated carbon prepared above with silicon particles deposited on it showed that the distribution concentration of the silicon particles deposited on the surface of the activated carbon was about 5wt%, and the distribution concentration of the silicon particles deposited inside the activated carbon was about 15wt%; in addition, the average particle size of the silicon particles inside the activated carbon was about 10nm, and the average particle size of the silicon particles on the surface of the activated carbon was about 5nm.

[0065] (3) placing the first intermediate material prepared above in a nitrogen atmosphere containing 1% oxygen for pre-oxidation treatment at a temperature of 300° C. for 1 h, so as to oxidize the silicon on the surface of the silicon particles into silicon dioxide, thereby obtaining a second intermediate material;

[0066] (4) using chemical vapor deposition to carbon-coat the second intermediate material, wherein the carbon source used is acetylene, the acetylene flow rate is 100 sccm, the coating time is 30 min, and a carbon coating layer with a thickness of about 10 nm is formed;

[0067] (5) Under argon atmosphere, the carbon-coated product was heat treated at a temperature of 900° C. for 2 hours to obtain a silicon-carbon composite material.

[0068] Example 2

[0069] Example 2 is basically the same as Example 1, except that before the activated carbon is immersed in the copper nitrate solution, the surface of the activated carbon is oxidized, which specifically includes the following steps:

[0070] Take the specific surface area as 1500m 2 / g of activated carbon, immerse the activated carbon in a nitric acid solution with a concentration of 65wt% to obtain a mixture, and the liquid-to-solid ratio of the mixture is 20:1 (mL / g); the mixture is refluxed and stirred at 80°C for 6 hours; after the reaction is completed, the mixture is cooled to room temperature, and the activated carbon after oxidation treatment is filtered with deionized water, and repeatedly washed until the filtrate is neutral, and the washed activated carbon is placed in an oven at 105°C for 12 hours. The activated carbon material treated with oxide is used for subsequent impregnation treatment, and the rest is implemented in the same way as in Example 1.

[0071] The above-mentioned chemical modification makes the surface of activated carbon have carboxyl and phenolic hydroxyl groups. These groups can regulate the adsorption behavior of activated carbon on the catalyst, making it easier for copper ions to be evenly adsorbed on the surface and internal pores of activated carbon, thereby further optimizing the gradient distribution structure of the catalyst.

[0072] Example 3

[0073] Example 3 is basically the same as Example 1, except that when the activated carbon is immersed in the copper nitrate solution, a porous polymer film is used to coat the activated carbon, which specifically includes the following steps:

[0074] Take 20g of a degradable polylactic acid porous polymer film (pore size 5.2nm), wrap the activated carbon in the porous polymer film to form an inclusion, and then immerse the inclusion in a copper nitrate solution, the immersion process is the same as in Example 1. After the immersion is completed, take out the inclusion for subsequent pyrolysis treatment, the polylactic acid porous film automatically decomposes during the pyrolysis process, and the copper nitrate is converted into a copper catalyst.

[0075] The use of porous polymer membranes to wrap carbon materials and then impregnate them can control the penetration rate of the catalyst precursor solution, preventing the precursor solution from quickly penetrating the carbon material without forming a gradient concentration. In addition, during the high-temperature pyrolysis process, the polymer will automatically decompose and will not affect the final product.

[0076] Example 4

[0077] Embodiment 4 provides a silicon-carbon composite material and a preparation method thereof, which specifically comprises the following steps:

[0078] (1) Take the specific surface area as 2000m 2 / g of porous carbon, immersing it in a 0.05mol / L nickel nitrate solution for 2h, and then transferring it to a 0.55mol / L nickel nitrate solution for immersion for 0.5h, maintaining the temperature of the nickel nitrate solution at 40°C during the immersion process, to obtain a porous carbon material containing nickel nitrate; in a nitrogen atmosphere, pyrolyzing the porous carbon material containing nickel nitrate at 400°C for 5h to convert the nickel nitrate therein into a nickel catalyst, to obtain a porous carbon containing a nickel catalyst;

[0079] The cross-sectional SEM-EDS analysis of the porous carbon material containing nickel catalyst prepared above shows that nickel therein has a gradient concentration characteristic, the nickel concentration on the surface of the porous carbon is about 1.2wt%, and the nickel concentration inside the porous carbon is about 4.8wt%;

[0080] (2) placing the porous carbon material containing nickel catalyst prepared above in a PECVD reaction chamber, and alternately introducing silane and nitrogen by pulsed gas inlet, with a gas flow ratio of silane to nitrogen of 1:20; setting the RF power to 500 W, the deposition temperature to 600 ° C, and the total deposition time to 5 hours; the pulse time is 15 seconds for silane and 45 seconds for nitrogen, and the reaction obtains porous carbon with silicon particles deposited, which is recorded as the first intermediate material;

[0081] EDS line scan characterization analysis of the porous carbon prepared as above and deposited with silicon particles showed that the distribution concentration of silicon particles deposited on the surface of the porous carbon was about 5wt%, and the distribution concentration of silicon particles deposited inside the porous carbon was about 15wt%; in addition, the average particle size of the silicon particles inside the porous carbon was about 6.5nm, and the average particle size of the silicon particles on the surface of the porous carbon was about 4nm.

[0082] (3) placing the first intermediate material prepared above in an argon atmosphere containing 0.1 wt% oxygen for pre-oxidation treatment at a temperature of 200° C. for 0.5 h, so as to oxidize the silicon on the surface of the silicon particles into silicon dioxide, thereby obtaining a second intermediate material;

[0083] (4) using chemical vapor deposition to carbon-coat the second intermediate material, wherein the carbon source used is acetylene, the acetylene flow rate is 250 sccm, the temperature is 700° C., the coating time is 90 min, and a carbon coating layer with a thickness of about 15 nm is formed;

[0084] (5) Under nitrogen atmosphere, the carbon-coated product was heat treated at a temperature of 1100° C. for 5 hours. After the heat treatment, it was pickled with a 0.5 mol / L hydrochloric acid solution for 1 hour to remove residual metal impurities, thereby obtaining a silicon-carbon composite material.

[0085] Example 5

[0086] Example 5 is basically the same as Example 4, except that the specific surface area is 2000m 2 / g of porous carbon was immersed in a 0.05mol / L nickel nitrate solution for 2h, and then nickel nitrate was added to the solution in batches to gradually increase the concentration of nickel nitrate in the solution, and the nickel nitrate was increased by 0.1mol / L every 30min until the nickel nitrate concentration reached 0.55mol / L, and the immersion was maintained at 0.55mol / L for 2h; in this process, the nickel nitrate solution was heated from room temperature to 80°C at a heating rate of 2°C / min to obtain a porous carbon material containing nickel nitrate; in a nitrogen atmosphere, the porous carbon material containing nickel nitrate was pyrolyzed at 400°C for 5h to convert the nickel nitrate therein into a nickel catalyst to obtain a porous carbon containing a nickel catalyst.

[0087] The cross-sectional SEM-EDS analysis of the porous carbon material containing nickel catalyst prepared above shows that the nickel therein has a more significant gradient concentration characteristic: the nickel concentration on the surface of the porous carbon is 0.8wt%, and the nickel concentration inside the porous carbon is 5.2wt%, that is, the mass ratio of the nickel catalyst inside the porous carbon to the nickel catalyst on the surface is about 6.5:1. Compared with Example 4, the dynamic impregnation method makes the nickel enrichment inside the porous carbon higher and the gradient distribution more obvious. This stronger gradient distribution helps to further improve the depth and uniformity of subsequent silicon deposition.

[0088] Example 6

[0089] Example 6 provides a silicon-carbon negative electrode material and a preparation method thereof, which specifically comprises the following steps:

[0090] (1) Take the specific surface area as 3000m 2 / g of porous carbon material, immersing it in a 0.01mol / L nickel nitrate solution for 6h, and then transferring it to a 0.8mol / L nickel nitrate solution for immersion for 1h, maintaining the temperature of the nickel nitrate solution at 60°C during the immersion process, to obtain a carbon material containing nickel nitrate; in a nitrogen atmosphere, pyrolyzing the carbon material containing nickel nitrate at 900°C for 3h to convert the nickel nitrate therein into a nickel catalyst, to obtain a carbon material containing a nickel catalyst;

[0091] (2) placing the carbon material containing nickel catalyst prepared above in a PECVD reaction chamber, and alternately introducing silane and nitrogen by pulsed gas inlet, with a gas flow ratio of silane to nitrogen of 1:5; setting the RF power to 50 W, the deposition temperature to 300 ° C, and the total deposition time to 30 min; the pulse time is 15 seconds for silane and 45 seconds for nitrogen, and the reaction obtains porous carbon with silicon particles deposited thereon, which is recorded as the first intermediate material;

[0092] (3) placing the first intermediate material prepared above in an argon atmosphere containing 5 wt% oxygen for pre-oxidation treatment at a temperature of 400° C. for 4 h, so as to oxidize the silicon on the surface of the silicon particles into silicon dioxide, thereby obtaining a second intermediate material;

[0093] (4) using chemical vapor deposition to carbon-coat the second intermediate material, wherein the carbon source used is acetylene, the acetylene flow rate is 50 sccm, the temperature is 700° C., the coating time is 40 min, and a carbon coating layer of about 3 nm thick is formed;

[0094] (5) Under nitrogen atmosphere, the carbon-coated product was heat treated at 800°C for 1 hour. After the heat treatment, it was pickled with 0.5 mol / L hydrochloric acid solution for 1 hour to remove residual metal impurities, thereby obtaining a silicon-carbon composite material.

[0095] Example 7

[0096] Example 7 is basically the same as Example 6, with the only difference being the pyrolysis process: in a nitrogen atmosphere, the carbon material containing nickel nitrate is first pyrolyzed at 600°C for 1.5 hours, and then heated to 900°C for 1.5 hours to convert the nickel nitrate therein into a nickel catalyst, thereby obtaining a carbon material containing a nickel catalyst.

[0097] Comparative Example 1

[0098] Comparative Example 1 provides a silicon-carbon composite material and a preparation method thereof, which specifically comprises the following steps:

[0099] (1) Take the specific surface area as 1500m 2 / g of activated carbon was immersed in a 0.5 mol / L copper nitrate solution for 8 hours, and the solution temperature was maintained at 50°C during the entire impregnation process to obtain an activated carbon material containing copper nitrate; in a nitrogen atmosphere, the activated carbon material containing copper nitrate was pyrolyzed at 600°C for 1 hour to convert the copper nitrate therein into a copper catalyst to obtain activated carbon containing a copper catalyst.

[0100] The cross-sectional SEM-EDS analysis of the activated carbon material containing the copper catalyst prepared above showed that the copper distribution was relatively uniform, the copper content on the surface of the activated carbon was 2.1wt%, and the copper content inside the activated carbon was 2.3wt%;

[0101] (2) The activated carbon material containing the copper catalyst prepared above is placed in a PECVD reaction chamber, and silane and argon are introduced simultaneously by continuous gas intake, with a gas flow ratio of silane to argon of 1:10; the RF power is set to 200 W, the deposition temperature is set to 450°C, and the total deposition time is set to 2 hours. The reaction obtains activated carbon deposited with silicon particles, which is recorded as the first intermediate material.

[0102] EDS line scan characterization analysis of the activated carbon prepared above with silicon particles deposited on it showed that the distribution concentration of silicon particles deposited on the surface of the activated carbon was 9wt%, and the distribution concentration of silicon particles deposited inside the activated carbon was 11wt%, that is, the mass ratio of silicon particles inside the activated carbon to silicon particles on the surface was about 1.2:1; and the particle size of silicon particles inside and on the surface of the activated carbon was about 7-8nm.

[0103] Steps (3) to (5) are the same as those in Example 1.

[0104] Comparative Example 2

[0105] The difference between Comparative Example 2 and Example 1 is that the first intermediate material is not subjected to pre-oxidation treatment, that is, the silicon-carbon composite material prepared in Comparative Example 1 does not contain a silicon dioxide layer. The rest is the same as Example 1.

[0106] The same method as in Example 1 was used to characterize the gradient distribution of the catalyst and silicon particles in the above examples and comparative examples, and the particle size of the silicon particles and the thickness of each layer in each silicon-carbon composite material were also detected. The test results are shown in Table 1.

[0107] Table 1 Relevant structural features of silicon-carbon composite materials in the relevant embodiments and comparative examples of the present invention

[0108]

[0109] The silicon-carbon composite material prepared in the above embodiment and comparative example is used to prepare a lithium ion battery, which specifically includes the following steps:

[0110] The silicon-carbon composite material in the above embodiment and comparative example is mixed with a conductive agent and a binder in a mass ratio of 90:5:5 to form a negative electrode slurry; wherein the conductive agent is acetylene black and the binder is polyvinylidene fluoride (PVDF); the negative electrode slurry is coated on a copper foil current collector to form a negative electrode active material layer with a thickness of 50 μm, thereby obtaining a negative electrode sheet;

[0111] LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811) is the positive electrode;

[0112] The polyethylene (PE) porous membrane was used as the separator with a thickness of 20 μm;

[0113] The electrolyte is a mixed solution of 1M LiPF6 dissolved in EC / DMC / EMC (volume ratio 1:1:1), and 2% VC (vinylene carbonate) is added as an additive.

[0114] The negative electrode, positive electrode, separator and electrolyte were assembled into a battery, and the relevant performance of the battery was tested. The test results are shown in Table 2.

[0115] Table 2 Performance of lithium-ion batteries prepared in the examples of the present invention and comparative examples

[0116]

[0117]

[0118] In combination with Examples 1-7, it can be seen that the lithium-ion battery of the silicon-carbon composite material prepared by the technical solution of the present invention has better first charge capacity, first coulomb efficiency, cycle retention rate and 2C charge capacity retention rate.

[0119] By comparing Example 1 and Comparative Example 1, it can be seen that the copper catalyst inside the activated carbon formed by the conventional impregnation method in Comparative Example 1 is relatively uniform, and does not show obvious catalyst concentration characteristics. The silicon particles in the first intermediate material prepared on this basis do not have obvious gradient concentration distribution characteristics and particle size difference distribution characteristics. At this time, the 600-week cycle retention rate and 2C charging capacity retention rate of the lithium-ion battery decrease, which proves that the distribution of silicon particles in the silicon-carbon composite material provided in the present invention is beneficial to improving the cycle life, rate performance and capacity retention rate of the battery.

[0120] By comparing Example 1 and Comparative Example 2, it can be seen that when the silicon-carbon composite material of Comparative Example 2 does not contain a silicon dioxide layer, the battery's first coulombic efficiency, cycle retention rate and charge capacity retention rate all decrease. This may be because the silicon dioxide layer and the carbon coating layer can synergistically alleviate the volume expansion of silicon during the charge and discharge process and improve the stability of the electrode structure.

[0121] In summary, the silicon-carbon composite material prepared by the present invention exhibits excellent electrochemical properties, including high specific capacity, good cycle stability and rate performance, through the regulation of the preparation process. From an environmental perspective, the use of the gas phase method to prepare avoids the environmental pollution problems that may be caused by the liquid phase method, reflecting the environmental friendliness of the process. Finally, the preparation method provided by the present invention can use common raw materials and equipment, the process is relatively simple, and has good industrialization potential and cost-effectiveness. These comprehensive advantages make this technical solution have important practical significance in the research and application fields of high-performance silicon-based negative electrode materials.

[0122] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0123] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0124] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.

Claims

1. A silicon-carbon composite material, characterized in that: include: Porous carbon materials; Silicon particles, wherein the silicon particles are distributed in the surface layer and the pores inside the porous carbon material, and the distribution concentration of the silicon particles in the surface layer of the porous carbon material is less than the distribution concentration of the silicon particles inside the porous carbon material, and the particle size of the silicon particles in the surface layer of the porous carbon material is less than the particle size of the silicon particles inside the porous carbon material; A silicon dioxide layer formed on the surface of the silicon particles; A carbon coating layer is formed at least on the surface of the silicon dioxide layer.

2. The silicon-carbon composite material according to claim 1, characterized in that: The thickness of the surface layer of the porous carbon material is 1 to 10% of the diameter of the porous carbon material, and the interior of the porous carbon material is the area of ​​the porous carbon material excluding the surface layer; And / or, the diameter of the porous carbon material is 1-10 μm, the region of the porous carbon material that is 0-100 nm away from the surface thereof is the surface layer of the porous carbon material, and the region that is more than 100 nm away from the surface of the porous carbon material is the interior of the porous carbon material; And / or, the ratio of the silicon particles on the surface of the porous carbon material to the silicon particles inside the porous carbon material is 1:2 to 1:5; And / or, the ratio of the total mass of silicon particles contained in the silicon-carbon composite material to the mass of the porous carbon material is 0.5:1 to 2:1; And / or, the particle size of the silicon particles on the surface of the porous carbon material is 1 to 5.8 nm, and the particle size of the silicon particles inside the porous carbon material is 1 to 11.2 nm; And / or, the specific surface area of ​​the porous carbon material is 500 to 3000 m 2 / g; And / or, the total pore volume of the porous carbon material is 0.6 to 1.2 cm 3 / g, the proportion of micropores with a pore size of less than 2 nm in the porous carbon material is 40-60% of the total pore volume of the porous carbon material, the proportion of mesopores with a pore size of 2-50 nm is 30-50% of the total pore volume of the porous carbon material, and the proportion of macropores with a pore size greater than 50 nm is 5-15% of the total pore volume of the porous carbon material; And / or, the thickness of the silicon dioxide layer is 1 to 2 nm; And / or, the carbon coating layer has a thickness of 2 to 30 nm.

3. A method for preparing a silicon-carbon composite material, characterized in that: include: Loading a catalyst on the surface and inside of the porous carbon material, wherein the concentration of the catalyst in the surface of the porous carbon material is lower than the concentration of the catalyst inside the porous carbon material, to obtain a porous carbon material containing a gradient concentration of catalyst; Silicon particles are deposited on the porous carbon material containing the gradient concentration catalyst by a vapor deposition method, thereby obtaining a first intermediate material; the silicon particles in the first intermediate material are distributed in the surface layer and the pores inside the porous carbon material, and under the action of the gradient concentration catalyst, the distribution concentration of the silicon particles in the surface layer of the porous carbon material is less than the distribution concentration of the silicon particles inside the porous carbon material, and the particle size of the silicon particles in the surface layer of the porous carbon material is less than the particle size of the silicon particles inside the porous carbon material; Performing a pre-oxidation treatment on the first intermediate material so that the silicon on the surface of the silicon particles is oxidized to form a silicon dioxide layer, thereby obtaining a second intermediate material; The second intermediate material is carbon-coated to form a carbon coating layer on the silicon dioxide layer to obtain a silicon-carbon composite material.

4. The preparation method according to claim 3, characterized in that: The method for loading the catalyst on the surface and inside of the porous carbon material specifically includes: first immersing the porous carbon material in a solution containing 0.01-0.1 mol / L of a catalyst precursor for 2-6 hours, and then immersing it in a solution containing 0.5-1 mol / L of a catalyst precursor for 0.5-2 hours; and controlling the temperature of the solution to 20-80° C. during the immersion process to obtain a porous carbon material containing a catalyst precursor; pyrolyzing the porous carbon material containing the catalyst precursor to convert the catalyst precursor therein into a catalyst, and obtaining a porous carbon material containing a gradient concentration catalyst; Alternatively, the method for loading the catalyst on the surface and interior of the porous carbon material specifically includes: first immersing the porous carbon material in a solution containing 0.01-0.1 mol / L of a catalyst precursor, and then adding the catalyst precursor to the solution at intervals of 15-30 minutes until the concentration of the catalyst precursor in the solution reaches 0.2-1 mol / L, and maintaining the immersion at the final concentration for 2-6 hours; during the immersion process, raising the temperature of the solution from room temperature to 60-80°C at a heating rate of 2-5°C / min; and pyrolyzing the porous carbon material containing the catalyst precursor to convert the catalyst precursor therein into a catalyst to obtain a porous carbon material containing a gradient concentration catalyst.

5. The preparation method according to claim 4, characterized in that: Before immersing the porous carbon material in a solution containing a catalyst precursor, the method further includes modifying oxygen-containing functional groups and / or nitrogen-containing functional groups on the porous carbon material; and / or, before the porous carbon material is immersed in the solution containing the catalyst precursor, the porous carbon material is wrapped with a porous polymer film having a pore size of 3 to 20 nm to form an inclusion, and then the inclusion is immersed in the solution containing the catalyst precursor; And / or, the pyrolysis treatment is carried out under inert atmosphere conditions, the pyrolysis treatment temperature is 400-900° C., and the time is 1-5 hours.

6. The preparation method according to claim 3, characterized in that: The catalyst comprises copper and / or nickel; And / or, the mass concentration ratio of the catalyst in the surface layer of the porous carbon material to the catalyst inside thereof is 1:2 to 1:10; And / or, the vapor deposition method includes plasma enhanced chemical vapor deposition, and the process conditions of the plasma enhanced chemical vapor deposition include: using a pulsed gas intake method, alternately introducing a reaction gas containing a gaseous silicon source and an inert gas, and the gas flow ratio of the reaction gas to the inert gas is 1:5 to 1:20; the radio frequency power used is 50 to 500 W, the pulse time is 1 to 60 seconds, the deposition temperature is 300 to 600 ° C, and the deposition time is 30 minutes to 5 hours; And / or, the pre-oxidation treatment comprises: placing the first intermediate material in an atmosphere with an oxygen content of 0.1 to 5 wt%, and pre-oxidizing it at a temperature of 200 to 400° C. for 0.5 to 4 hours; And / or, the carbon coating method includes chemical vapor deposition, and the process conditions of the chemical vapor deposition method include: a flow rate of a gaseous carbon source of 50 to 250 sccm, a temperature of 700 to 950° C., and a time of 10 to 90 min; And / or, the preparation method further includes post-processing, and the post-processing includes: heat-treating the obtained silicon-carbon composite material under inert atmosphere conditions, and the heat-treatment temperature is 800-1100° C. and the time is 1-5 hours.

7. A silicon-carbon composite material, characterized in that: The method is prepared by the method described in any one of claims 3 to 6.

8. Use of the silicon-carbon composite material according to claim 1, 2 or 7 in preparing a secondary battery negative electrode or a secondary battery.

9. A negative electrode for a lithium ion battery, characterized in that: It comprises a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector, wherein the negative electrode active material layer comprises the silicon-carbon composite material according to claim 1, 2 or 7.

10. A lithium ion battery comprising a positive electrode, a negative electrode, an electrolyte and a separator, characterized in that: The negative electrode is the negative electrode of the lithium ion battery according to claim 9.

Citation Information

Cited By

  • Silicon-carbon-based composite material, preparation method and application of silicon-carbon-based composite material in lithium ion battery

    CN120072918A

  • Porous silicon-carbon composite material as well as preparation method and application thereof

    CN121260750A

  • Low-expansion and high-capacity silicon-carbon composite negative electrode material and preparation method thereof

    CN121405065A

  • Silicon-carbon composite material, preparation method thereof, electrode and battery

    CN121687929A